2022
DOI: 10.1021/acsbiomaterials.1c01579
|View full text |Cite
|
Sign up to set email alerts
|

Nontoxic In Vivo Clearable Nanoparticle Clusters for Theranostic Applications

Abstract: Disintegrable inorganic nanoclusters (GIONs) with gold seed (GS) coating of an iron oxide core with a primary nanoparticle size less than 6 nm were prepared for theranostic applications. The GIONs possessed a broad near-infrared (NIR) absorbance at ∼750 nm because of plasmon coupling between closely positioned GSs on the iron oxide nanoclusters (ION) surface, in addition to the ∼513 nm peak corresponding to the isolated GS. The NIR laser-triggered photothermal response of GIONs was found to be concentration-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The kidney poses a critical physiological barrier to filtering blood components based on size cut-off. The factors, such as the size of d -penicillamine-stabilized Au NCs being less than 6 nm and a steady near-neutral zeta potential, favor them toward renal clearance. , ICP–MS analysis of various organs 24 h post-injection showed a high gold accumulation (∼34% ID/g) in the kidneys compared to that in the liver and spleen (Figure B). This result correlates with reported urinary clearance of DPA and similarly sized metal NCs after possible evasion of any protein fouling and aggregation during peripheral circulation.…”
Section: Resultsmentioning
confidence: 99%
“…The kidney poses a critical physiological barrier to filtering blood components based on size cut-off. The factors, such as the size of d -penicillamine-stabilized Au NCs being less than 6 nm and a steady near-neutral zeta potential, favor them toward renal clearance. , ICP–MS analysis of various organs 24 h post-injection showed a high gold accumulation (∼34% ID/g) in the kidneys compared to that in the liver and spleen (Figure B). This result correlates with reported urinary clearance of DPA and similarly sized metal NCs after possible evasion of any protein fouling and aggregation during peripheral circulation.…”
Section: Resultsmentioning
confidence: 99%
“…However on Day 28, all the organs including liver possessed only marginal quantity (0.08% ID/g for liver and spleen) of MQCNS. While prior reports show that kidney is the most preferred route of excretion for nanoparticles with size less than 6-8nm [41][42][43], albumin stabilized AuQCs is an exception due to its retention from passing through healthy glomerular basal membrane [44]. While there is no single pathway of albumin degradation, most studies have reported that GI tract is a significant site of albumin catabolism (~ 40-70%) in normal individuals [45].…”
Section: Pre-clinical Safety Assessment and Biodistribution Of Mqcnsmentioning
confidence: 99%
“…These results confirmed the biodegradability of HPIO@ZDS and its rapid clearance by the kidney. Similarly, Pranjali et al designed and synthesized iron oxide and gold NPs assembled into decomposable nanoclusters, which decompose under physiological conditions and are cleared through both hepatobiliary and renal pathways (Yadav et al, 2022). These biodegradable NPs provide an exciting opportunity for the design of kidney‐clearable NPs.…”
Section: Factors Affecting the Renal Clearancementioning
confidence: 99%